Parnasianism: An Attempt Existence Aesthetics To Literature - Zahratul Aini; Awwalul Abidin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This article discusses one of the sects that emerged in the development of Arabic literature, namely Parnasianism (Barnasiyah). This research aims to discuss matters related to the flow of Parnasianism (Barnasiyah). both in terms of history, figures, vision and mission, urgency, characteristics and examples of application. This research is a descriptive qualitative method, The data collection method used the listening method with a follow up technique, namely the note taking technique. The results obtained from this study are history of the emergence and development of the Parnasianism (Barnasiyah). sect in the second half of the 19th century. The adherents of this sect holds that the most important thing about a work of literature is that its aesthetic is not bound by ethics, morals or religion. Because according to them, the purpose of art is for art itself and nothing else. And one of the figures who realised this flow was Nizar Qabbani in his poem entitled Asy-syaqiqatan.